Efeitos do exercício físico sobre a expressão hepática de activina A e folistatina em modelo de doença hepática gordurosa não acoólica em ratos - Silva, Rafaella Nascimento e (Universidade Federal de São Carlos, 2012)
Nonalcoholic Fatty Liver disease (NAFLD) is characterized by fat accumulation in the liver and associated with obesity and insulin resistance. Activin A is a member of the transforming growth factor (TGF)-β superfamily which inhibits hepatocyte growth and induces apoptosis. Follistatin is a glycoprotein which antagonizes the biological actions of activin. Exercise is an important therapeutic strategy to decrease the metabolic effects of obesity. In this study, we evaluated the pattern of Activin A and follistatin liver expression in obese rats submitted to swimming exercise. Adult male Wistar rats were allowed free access to standard rodent chow (control group, C) or HF diet (58% Kcal from fat, high-fat group, HF) during 12 weeks. Glucose tolerance test (GTT) and insulin tolerance test (ITT) were performed at 12 weeks. After 12 weeks, C and HF rats were randomly assigned to a swimming training group (C-Ex and HF-Ex) or a sedentary group (C-Sed and HF-Sed). C-Ex and HF-Ex swam for 45 minutes at 0900h and 1700h, 5 day week-1, for 4 weeks. After this period, rats were submitted again to GTT and then killed by decapitation. Plasma was collected for liver enzymes, alanine transaminase (ALT), aspartate transaminase (AST) and gammaglutamyl transaminase (GGT) determination. Liver was dissected and immediately frozen in liquid nitrogen and stored at -700 C for subsequent analysis. Actvin βA subunit and follistatin mRNA was quantified by real time RT-PCR. HF developed insulin resistance according to GTT and ITT tests. ALT levels were significantly higher in HF-Sed than in C-Sed and significantly lower in HF-Ex than in HF-Sed. AST and GGT did not vary among the groups. Actvin βA subunit mRNA was significantly higher in HF-Ex than in HF-Sed. Follistatin mRNA was significantly lower in C-Ex and HF-Ex compared to C-Sed and HF-Sed, respectively. There was no evidence of steatosis or inflammation (grade 0) in C. In contrast, in HF the severity of steatosis varied from grade 1 to grade 3. This was not associated with inflammation or fibrosis. After the training period, HF-Ex showed improvement in the extent of liver parenchyma damage, the severity of steatosis varying from grade 0 to grade 1. These data suggest that exercise may reduce the deleterious effects of high-fat diet on liver and the local expression of activin-follistatin may be involved.
Keywords: Obesidade; Activina; Folistatina; Fígado - doenças; Exercício físico; Doença hepática gordurosa não alcoólica (DHGNA); Nonalcoholic fatty liver disease (NAFLD); Activin-follistatin; Exercise; CIENCIAS DA SAUDE::FISIOTERAPIA E TERAPIA OCUPACIONAL